PROGRAM PEMBERDAYAAN MASYARAKAT MELALUI NILAI-NILAI BUDAYAMARITIM BERBASIS KEARIFAN LOKAL SEBAGAI UPAYA PENINGKATANKESEJAHTERAAN EKONOMI MASYARAKAT KEPULAUAN SERIBU - Setiawati, Rahmi; Safitri, Karin Amelia (Jurnal Vokasi Indonesia, 2020)
The Thousand Islands are islands that are famous for their maritime territory. Development through cultural values in these islands needs to be done, namely with a technological approach. The technological aspect approach as an information center from the results of the internalization of maritime culture with local wisdom, cultural value products can produce products in the form of physical, which consists of art, culinary, building art (architecture) and non-physical in the form of maritime norms and values, which then become an attraction for information both from the element of tourism and the implementation of maritime culture which has economic value. The research method used qualitative with the technique of collecting through interviews, observation and document study. The results of this study indicate that the community development program is an important factor in increasing the capacity of the community through the formation of public awareness by forming behavior patterns in the application of a sustainable maritime culture, which can make the community prosperous. This is in line with the strengthening of the people of Kelapa Island, with the awareness of having a maritime area, it will develop the spirit to defend the maritime area, which is in accordance with the characteristics of Kelapa Island, so that it can improve the welfare of its people, through people's economic efforts with marine production and development of social aspects. , physically and culturally, will be created. However, maritime culture technology is needed which will produce a community-based information network prototype, as a means of information about maritime cultural values, so that it will strengthen the coconut island as marine tourism in accordance with local wisdom.